Writing Scientific Biography - Greene, Mott T. (Journal of the history of biology, 2007)
Much writing on scientific biography focuses on the legitimacy and utility of this genre. In contrast, this essay discusses a variety of genre conventions and imperatives which continue to exert a powerful influence on the selection of biographical subjects, and to control the plot and structure of the ensuing biographies. These imperatives include the following: the plot templates of the Bildungsroman (the realistic novel of individual self-development), the life trajectories of Weberian ideal types, and the functional elements and personae of the folkloric tale of the "hero's quest." The essay discusses the nature and application of these genre conventions in some detail, with the conclusion that biography, however useful, exerts a powerfully distorting influence on the image of how most science gets done.